Las técnicas de trabajo grupal y su incidencia en el logro de aprendizajes significativos en los estudiantes del colegio experimental universitario “Manuel Cabrera Lozano”, matriz, barrio la Argelia, parroquia San Sebastián, cantón Loja, período 2007-2008. Lineamientos propositivos - Medina Cabrera, Beatriz María (2009)
The present work, referred to The Techniques of Work Group and their Incidence in the Achievement of Significant Learnings in the Students of the School Experimental University student "Manuel Goatherd Lozano", womb, neighborhood The Algeria, parish San Sebastian, canton Loja, period 2007-2008. Limits Proposition, presents a truthful study of this educational reality, with the purpose of determining the relationship that exists among these two categories. To be able to fulfill that manifested he/she thought about the following General Objective: - To cooperate to the invigoration of the academic level of the School Experimental University student "Manuel Goatherd Lozano" through a better use and application of the different technical groups, so that it achieves the acquisition of significant learnings. Compliment the whole investigation process, you ends up determining that a narrow relationship exists between the work group and the significant learnings. A dialectical logic was continued in its development process where had the active participation of the curricular fellows that you/they were selected for the present work. To the study object and investigation, he/she took it in all their parts, to know it closely and, this way, to arrive to satisfactory results that allow to offer a formation of quality and that he/she responds to the institutional, personal, social and community requirements. According to the project and according to the inductive method you arrived to general determinations according to the individual knowledge of the informants; the deductive method when particularizing the norms, principles, approach, etc., they allowed to formulate general approaches. The descriptive method for its rational interpretation and analysis of the picked up information allowed the confirmation of the hypothesis and the writing of the investigation report. The scientific method when allowing the analysis, the synthesis, the induction-deduction of the processes or investigation stages facilitated to arrive to the conclusions of the investigated problem. The results to those that you arrived are that is to say of a lot of importance for that you/they denote that the proposed objectives were completed, you ended up determining that the significant learnings are feasible of acquiring them by means of the work group. As basic conclusion it is determined that the techniques of work group are extremely important in the pedagogic process so that the students acquire significant learning